2018
DOI: 10.1111/1442-1984.12217
|View full text |Cite
|
Sign up to set email alerts
|

Variation in reproductive modes and population genetic structures of a monocarpic perennial herb, Cardiocrinum cordatum, in relation to habitat fragmentation

Abstract: Reproductive systems are recognized as having a profound influence on the extent and structure of genetic variation in plant populations. To investigate the spatiotemporal variation in the reproductive modes (sexual and vegetative reproduction) and population genetic structures of a monocarpic perennial herb, Cardiocrinum cordatum (liliaceae), we selected a variety of habitats (e.g. large forested area including primeval forest, small fragmented secondary forest, and so on) around Sapporo City, Japan. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Based on a long-term monitoring study, Araki, Shimatani, Nishizawa, Yoshizane, and Ohara (2010) and Ohara et al (2006) reported that flowering can start after the three-leaved rosette stage, and over 70% of five-leaved and sixleaved rosette plants flowered in the next season. In addition, Narumi and Ohara (2018) recently reported a high flowering probability of small rosette individuals found in several populations of C. cordatum var. glehnii (i.e.…”
Section: Methodsmentioning
confidence: 95%
“…Based on a long-term monitoring study, Araki, Shimatani, Nishizawa, Yoshizane, and Ohara (2010) and Ohara et al (2006) reported that flowering can start after the three-leaved rosette stage, and over 70% of five-leaved and sixleaved rosette plants flowered in the next season. In addition, Narumi and Ohara (2018) recently reported a high flowering probability of small rosette individuals found in several populations of C. cordatum var. glehnii (i.e.…”
Section: Methodsmentioning
confidence: 95%
“…Larger‐sized individuals had more numerous flowers; at HU‐1 plants had four to 20 flowers per plant and at HU‐2 plants had two to six flowers. In addition, at HU‐2, vegetative offshoot formation occurred with a lower frequency (Narumi & Ohara ). Control (CON): Individuals were left undamaged to determine resource allocation to sexual and vegetative reproduction in natural conditions. Outcross (OUT): Flowers were emasculated prior to anthesis and then hand‐pollinated with pollen collected from distant flowers. This treatment intended plants to use their resources for maximized seed production. Stigma cut (SC): Styles were cut off before anther dehiscence.…”
Section: Methodsmentioning
confidence: 99%
“…Largersized individuals had more numerous flowers; at HU-1 plants had four to 20 flowers per plant and at HU-2 plants had two to six flowers. In addition, at HU-2, vegetative offshoot formation occurred with a lower frequency (Narumi & Ohara 2018). 1.…”
Section: Resource Allocation Experimentsmentioning
confidence: 96%
See 2 more Smart Citations